THE DETERMINATION OF MERCURY (Hg) IN GREEN MUSSELS (Perna Viridis) USING REFLUX DIGESTION BY COLD VAPOUR ATOMIC ABSORPTION SPECTROPHOTOMETRY (CV-AAS) - Nisa, Atina Khoiron; Dewi, Diana C; Syarifah, Umaiyatus (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2023)
Green mussels, or Perna viridis, are a well-liked fishery product in the community. It can grow happily in a loch, seabord, or mangrove downstream. Through its eggshell, it takes in metals, including mercury (Hg). This study measures the effect of temperature and digestion composition on the amount of mercury (Hg) in green mussels using reflux digestion by cold vapour absorption spectrophotometry (CV-AAS). Utilizing Cold Vapour Atomic Absorption Spectrophotometry (CV-AAS) at a wavelength of 253,7 nm, the study's methodology entails figuring out the ideal digestion composition and temperature for various HNO3 p.a.: H2O2 p.a. destructor compositions (1:0; 2:1; 4:1; 10:3). The results of the investigation indicated that the optimal temperature was 800C. With a p-value (0,023) > a (0,05), the t-test result demonstrated a significant effect utilizing the variation in digestion composition. The general public can still safely consume green mussels from Muncar Beach because the sample, which was taken at the ideal temperature and with different digestion variations, contained 0.359 parts per million of mercury. The Indonesian National Standard's maximum limit is not met by these results.